2002
DOI: 10.1093/mutage/17.1.89
|View full text |Cite
|
Sign up to set email alerts
|

Detection of micronuclei, cell proliferation and hyperdiploidy in bladder epithelial cells of rats treated with o-phenylphenol

Abstract: o-Phenylphenol (OPP), a widely used fungicide and antibacterial agent, has been considered to be among the top 10 home and garden pesticides used in the USA. Earlier studies have consistently shown that the sodium salt of OPP (SOPP) causes bladder cancer in male Fischer 344 (F344) rats, whereas OPP has produced variable results. This difference has been attributed to the presence of the sodium salt. To determine cellular and genetic alterations in the rat bladder and the influence of the sodium salt, F344 rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 42 publications
2
16
0
Order By: Relevance
“…OPP and PHQ, however, may cause chromosomal damage, i.e. chromosome aberrations, micronuclei, sister-chromatid exchange and aneuploidy (Tayama-Nawai et al, 1984;Tayama et al, 1989;Balakrishnan et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…OPP and PHQ, however, may cause chromosomal damage, i.e. chromosome aberrations, micronuclei, sister-chromatid exchange and aneuploidy (Tayama-Nawai et al, 1984;Tayama et al, 1989;Balakrishnan et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Induction of micronuclei in rat urinary bladder cells by OPP, as reported by Balakrishnan et al [2002], provides evidence for an association between the formation of bladder tumors and simple chromosome breakage. Addi-tional support for this association was also found in an earlier study reported by Tadi-Uppala et al [1996], in which OPP, SOPP, NaCl, or OPP plus NaCl were administered to rats in their diet.…”
Section: In Vivo Mammalian Systems Detecting Chromosomal Damagementioning
confidence: 71%
“…PHQ tested in the absence of PHS did not induce micronuclei in their studies. These results were initially encouraging, but in follow-up in vivo clastogenicity studies designed to detect aneuploidy [Balakrishnan et al, 2002;Balakrishnan and Eastmond, 2003], micronuclei were found, but there were no hyperdiploid (potential aneuploid) cells in male rat bladder epithelial cells exposed to carcinogenic dose levels of OPP. Although the studies do not rule out the induction of aneuploidy by chromosome loss, the induction of neoplasia through specific chromosome aneuploidy does not appear likely.…”
Section: In Vitro Mammalian Systems Detecting Chromosomal Damagementioning
confidence: 99%
See 2 more Smart Citations